Plasmid-mediated antimicrobial resistance across One Health sectors: transmission dynamics and surveillance needs - Nuha Fairusya; Rongxuan Wang; Ryo Honda (mSphere, 2026)
ABSTRACT Antimicrobial resistance (AMR) is increasingly recognized as a One Health challenge driven by the continuous exchange of resistant bacteria and resistance determinants across human, animal, and environmental sectors. While genomic surveillance has substantially improved detection of antimicrobial resistance genes (ARGs), most monitoring frameworks remain gene- or isolate-centric, limiting insight into the mechanisms that govern resistance transmission and persistence. Recent evidence indicates that plasmids, self-replicating mobile genetic elements (MGEs) capable of horizontal transfer across bacterial species, play an important role in disseminating clinically relevant resistance determinants across sectors. In this mini-review, we synthesize genomic and ecological evidence demonstrating that a limited number of plasmid incompatibility (Inc) groups recur across human, animal, and environmental reservoirs, often independent of bacterial host lineages. We highlight how plasmid transmission dynamics are shaped by host-independent mobility, ecological generalism, co-selection with accessory traits, and persistence in engineered and natural environments. We further examine why current AMR surveillance approaches, including ARG-centric metagenomics and isolate-based monitoring, systematically overlook these plasmid-mediated processes. Furthermore, we propose that plasmid-resolved analysis represents a critical and currently underutilized complementary layer for One Health AMR surveillance. Integrating plasmid classification and genomic reconstruction into wastewater-based epidemiology and cross-sector monitoring frameworks can improve attribution of transmission pathways, enhance early detection of high-risk resistance, and provide a mechanistic foundation for risk-informed intervention strategies.